2016
DOI: 10.4103/2231-0762.186798
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oral health status and treatment needs of Santhal tribes of Dhanbad District, Jharkhand

Abstract: Aims and Objectives:India has an assortment of tribal population living in isolated pockets, and the Santhals are numerically predominant in Jharkhand. This study was aimed at assessing the oral health status and treatment needs of Santhals residing in Dhanbad, Jharkhand.Materials and Methods:A cross-sectional survey of 921 Santhals of Topchanchi Block was conducted. A modified World Health Organization (WHO) Oral Health Assessment Form (1997) was utilized and examined according to the WHO methodology (1997). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
5
10
1
Order By: Relevance
“…The mean decayed, missing, and filled tooth (dmft) score was 1.12±2.27 in subjects 2–5 years old and in the higher age groups of 35–44 years & 65–74 years, the scores were 0.72±1.45 and 1.69±4.76 teeth, respectively. This was not in accordance with the findings of Kumar et al [19] where the prevalence was 3.56±1.93 and 5.21±2.34 and 7.42±4.29 teeth, respectively, as also in the studies by Maurya et al[24], Lang et al[25] and Jayashantha and Johnson [26], where the mean DMFT scores were quite high.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The mean decayed, missing, and filled tooth (dmft) score was 1.12±2.27 in subjects 2–5 years old and in the higher age groups of 35–44 years & 65–74 years, the scores were 0.72±1.45 and 1.69±4.76 teeth, respectively. This was not in accordance with the findings of Kumar et al [19] where the prevalence was 3.56±1.93 and 5.21±2.34 and 7.42±4.29 teeth, respectively, as also in the studies by Maurya et al[24], Lang et al[25] and Jayashantha and Johnson [26], where the mean DMFT scores were quite high.…”
Section: Discussioncontrasting
confidence: 75%
“…al. [19] where they were seen only in the age groups of 35–44 year (0.84) and 65–74 years (0.65) and by Kumar V et. al.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, the majority of the subjects (70.2%) who participated were males which is similar with the studies conducted by Padma and Sushi () (59.3%), Dhanappa et al () (58%) Kadanakuppe and Bhat () (59.3%) Vivek et al () (57.7%), Thaweboon et al () (53%) and Kumar et al () (60.8%). However contradictory results were found in studies carried out by Kumar, Dileep, Sethi, and Gupta (), Naheeda, Padma, and Paul () and Reddy CVK (Jyothi & Reddy, ) and Philip, Chithresan, Vijayaragavan, and Maradi () where majority of the subjects were females.…”
Section: Discussionsupporting
confidence: 90%
“…Several researches were done among the tribal population in India and the studies showed that the oral health status and oral hygiene practices were very poor among the tribal population from different states of India. [ 19 24 25 26 27 ]…”
Section: Introductionmentioning
confidence: 99%